2023
DOI: 10.1039/d3qm00216k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in MXenes: a promising 2D material for photocatalysis

Abstract: Photocatalysis is considered a promising technology for the current environmental crisis and high energy demand caused by industrialization development. However, the practical applications and solutions for conventional catalysts are restricted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 101 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…MXenes with the M n +1 X n T x formula (M: early transition metal, X: C and/or N, T x : functional groups, n = 1–4) are two-dimensional (2D) multilayered materials that recently emerged as cocatalysts for photocatalytic applications due to their unique structural and electronic properties. , As photocatalysts, the formed MXene-derived transition metal oxides (MO x ) can be highly efficient nanomaterials for photocatalytic applications. , MXene-derived MO x are obtained by partial or complete oxidation of MXene (Ti 3 C 2 T x and Ti 2 CT x ) depending on oxidation conditions, and they exhibit superior properties compared to MO x /MXene composites. , Recent advancements in MXene-based photocatalysts highlight their growing significance in environmental and energy challenges, and ongoing research aims to overcome the current limitations and scale up their production for practical applications. Reported studies pointed out that oxygen-containing functional groups, especially, facilitate the formation of MO x phases . It has been reported that TiO 2 /amorphous carbon sheets can be derived by using flash-heating multilayered Ti 3 C 2 T x in air .…”
Section: Introductionmentioning
confidence: 99%
“…MXenes with the M n +1 X n T x formula (M: early transition metal, X: C and/or N, T x : functional groups, n = 1–4) are two-dimensional (2D) multilayered materials that recently emerged as cocatalysts for photocatalytic applications due to their unique structural and electronic properties. , As photocatalysts, the formed MXene-derived transition metal oxides (MO x ) can be highly efficient nanomaterials for photocatalytic applications. , MXene-derived MO x are obtained by partial or complete oxidation of MXene (Ti 3 C 2 T x and Ti 2 CT x ) depending on oxidation conditions, and they exhibit superior properties compared to MO x /MXene composites. , Recent advancements in MXene-based photocatalysts highlight their growing significance in environmental and energy challenges, and ongoing research aims to overcome the current limitations and scale up their production for practical applications. Reported studies pointed out that oxygen-containing functional groups, especially, facilitate the formation of MO x phases . It has been reported that TiO 2 /amorphous carbon sheets can be derived by using flash-heating multilayered Ti 3 C 2 T x in air .…”
Section: Introductionmentioning
confidence: 99%
“…MXenes materials obtained by etching through water-soluble acid solutions, such as HF aqueous solutions, basically have surface functional groups such as -F, -OH, and -O. Recent studies have extended the chemical range (-O, -OH, and -F) of the complete or incomplete surface ends of MXenes to other elements (-N, -NH, -NH 2 , -S, -SH, -H, -Cl, -Br, and -I) [11] since it is considered to be an important parameter that controls the properties of MXenes. The substitution of -O for -OH and -F will lead to a wider bandgap, and the composition of the termination group is also important for controlling the work function of MXenes.…”
Section: Introductionmentioning
confidence: 99%